Feasibility and Acceptability of Self and Peer Evaluation In Objective Structured Practical Examination (OSPE) - Vijayalakshmi, K; Revathi, S; Venkatesan, L (Health Renaissance, 2015)
Background: Objective Structured Practical Examination (OSPE) is being widely used in the assessment of clinical performance of students in healthcare profession. Objective: This study was conducted to find out the feasibility and acceptability of Self and Peer-Evaluation in Objective Structured Practical Examination (OSPE) in Psychiatric nursing among Nursing Students. Methods: A cross sectional, descriptive correlational study was conducted at Apollo College of Nursing, Chennai among 84students of 3rd Year B.Sc Nursing in Psychiatric Nursing subject. Students were selected by using purposive sampling technique. OSPE consisting of 7 stations (using the predetermined check lists for each station) was conducted. Feedback was obtained from the students and teachers involved in evaluation, immediately after completing the evaluation by using 12 items feedback questionnaire. Data was analyzed by using Descriptive (Mean, frequency, percentage) and Inferential (t-test) statistics. Results: Self and Peer evaluation in OSPE in Psychiatric nursing among Nursing Students, was feasible to conduct. Most of the students and all the teachers have accepted these methods on its various aspects. Total mean acceptability scores of students and teachers were 40.43±6.33, 45.79±2.72/48 and 42.43±7.37, 44.64±1.76/48 in self and peer evaluation respectively. Conclusion: Students’ and teachers’ feedback are essential to implement any teaching learning activities including evaluation. Self and Peer Evaluation were feasible to conduct and well accepted by the students and teachers. DOI: http://dx.doi.org/10.3126/hren.v12i1.11984 Health Renaissance 2014;12(1):38-43